Genome-wide analysis of the Tritipyrum WRKY gene family and the response of TtWRKY256 in salt-tolerance - Li, Kuiyin; Liu, Xiaojuan; He, Fang; Chen, Songshu; Zhou, Guangyi; Wang, Yuhai; Li, Luhua; Zhang, Suqin; Ren, Mingjian; Yuan, Yuanyuan (Frontiers in Plant Science, 2022)
Introduction The transcription factor WRKY is widespread in the plant kingdom and plays a crucial role in diverse abiotic stress responses in plant species. Tritipyrum, an octoploid derived from an intergeneric cross between Triticum aestivum (AABBDD) and Thinopyrum elongatum (EE), is a valuable germplasm resource for introducing superior traits of Th. elongatum into T. aestivum. The recent release of the complete genome sequences of T. aestivum and Th. elongatum enabled us to investigate the organization and expression profiling of Tritipyrum WRKY genes across the entire genome. Results In this study, 346 WRKY genes, from TtWRKY1 to TtWRKY346, were identified in Tritipyrum. The phylogenetic analysis grouped these genes into three subfamilies (I-III), and members of the same subfamilies shared a conserved motif composition. The 346 TtWRKY genes were dispersed unevenly across 28 chromosomes, with 218 duplicates. Analysis of synteny suggests that the WRKY gene family may have a common ancestor. Expression profiles derived from transcriptome data and qPCR demonstrated that 54 TtWRKY genes exhibited relatively high levels of expression across various salt stresses and recovery treatments. Tel1E01T143800 (TtWRKY256) is extremely sensitive to salt stress and is on the same evolutionary branch as the salt-tolerant A. thaliana genes AtWRKY25 and AtWRKY33. From 'Y1805', the novel AtWRKY25 was cloned. The Pearson correlation analysis identified 181 genes that were positively correlated (R>0.9) with the expression of TtWRKY256, and these genes were mainly enriched in metabolic processes, cellular processes, response to stimulus, biological regulation, and regulation of biological. Subcellular localization and qRT-PCR analysis revealed that TtWRKY256 was located in the nucleus and was highly expressed in roots, stems, and leaves under salt stress. Discussion The above results suggest that TtWRKY256 may be associated with salt stress tolerance in plants and may be a valuable alien gene for improving salt tolerance in wheat.